Return to Play in Youth Athletes: Role of the Radiologist with Focus on the Upper Extremity - Patel, Vandan; Nguyen, Ngan P.; Brown, Naomi; Mendenhall, Shaun D.; Zoga, Adam C.; Nguyen, Jie C. (Seminars in Musculoskeletal Radiology, 2024)
Increase in youth sports participation, longer duration of play, and earlier starting points have increased the prevalence of acute and repetitive overuse musculoskeletal injuries. This rise in injury rates has led to increased efforts to better understand the susceptible sites of injury that are unique to the growing immature skeleton. Upper extremity injuries are currently the best studied, particularly those that occur among pediatric baseball players and gymnasts. The weak link in skeletally immature athletes is the growth plate complex that includes those injuries located at the epiphyseal and apophyseal primary physes and the peripherally located secondary physes. This article reviews the anatomy and function of these growth plate complexes, followed by a discussion of the pathophysiologic mechanisms, spectrum of imaging findings, and existing evidence-based guidelines for injury prevention and return to play.
Keywords: apophysitis; growth plate; pediatric athlete; return to play; physeal stress injury